Hubungan Dukungan Keluarga dengan Tingkat Kecemasan pada Lansia di Desa Panyusuhan Kecamatan Sukaluyu Kabupaten Cianjur - Cici Airin Destriyani; Khrisna Wisnu Sakti; Marisca Agustiana (NAJ Nursing Applied Journal, 2025)
Introduction. Family support is help, attention, and appreciation from other people or circumstances that make an individual feel loved. Family support needs, capacities, and sources change throughout a person's life. The family is the environment that individuals first become acquainted with in the socialization process. The same view regarding family support, Sarafino, who explains that family support is the pleasure received from attention, appreciation from other people or from environmental groups that provide this support (i.e. family, loved ones or community members) and assistance. The aim of research is to understand the relationship between family support and level of support. Anxiety among the elderly in Panyusuhan Village. The population size method in this research is 80 with a sample size of 66 taken using purposive sampling. This research is quantitative with a correlation type of design, namely research carried out to relate two variables. Research design: This research uses cross-sectional (cross-sectional) with an observational approach. Research Instrument: good family support 66 (63.6%) and poor family support 24 (36.4%) and normal anxiety level 16 (24.2%), mild 35 (53.0%) and moderate anxiety level 15 (22.7%). Bivariate analysis uses the chi square test. The conclusion is that there is a relationship between family support and the level of anxiety in the elderly in Panyusuhan Village, Sukaluyu District, Cianjur Regency in 2022, so that families can provide maximum family support to the elderly.